ANALISIS SEBARAN PRIORITAS KETAHANAN PANGAN DI WILAYAH KARESIDENAN BESUKI - Nadhirah, Aulia; Napitupulu, Tia Sofiani; Marseva, Amalia Dwi; Sumarlina, Sumarlina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The implementation of this research is to answer three questions, including: (1) measuring the score of the Food Security Index (IKP) in the Besuki Residency, (2) mapping the distribution of priority areas for food insecurity in the Besuki Residency, and (3) providing recommendations for overcoming food insecurity problems. The data used is secondary data collected from the publications of the Central Statistics Agency (BPS), the Health Service, and the Ministry of Home Affairs. Analysis of the score of the Food Security Index uses seven indicators that are classified into three aspects, namely aspects of food availability, aspects of food accessibility, and aspects of food utilization. The determination of priority groups for vulnerable category areas refers to the cut-off point of the Food Security Index. Determination of recommendations for handling the vulnerable category areas using quantitative and qualitative approaches. The results of the study showed that: (1) the score of the Food Security Index in Besuki Residency area is 85.28 and this score is included in resistant category (fifth priority), (2) the distribution of priorities for vulnerable category areas in Besuki Residency area is divided into three categories, namely very vulnerable, vulnerable and slightly vulnerable, and (3) there are programs that have been implemented by the East Java Provincial Government as an effort to overcome for vulnerable areas. However, in its implementation, it is still necessary to pay attention to the equity in all regions by considering the various conditions and resources of each region. In addition, there is a need for integrated supervision in its implementation, so that the policy can take place more measurably.